2017
DOI: 10.1002/ejp.1059
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and impact of childhood adversities and post‐traumatic stress disorder in women with fibromyalgia and chronic widespread pain

Abstract: Objective: This study investigates the prevalence of different types of childhood adversities (CA) and posttraumatic stress disorder (PTSD) in female patients with Fibromyalgia or Chronic Widespread Pain (FM/ CWP) compared to patients with Functional Dyspepsia (FD) and achalasia. In FM/CWP, we also investigated the association between CA and PTSD on the one hand and pain severity on the other. Methods: Patient samples consisted of 154 female FM/CWP, 83 female FD and 53 female achalasia patients consecutively r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 49 publications
4
33
1
1
Order By: Relevance
“…Additionally, theta scores were positively associated with PROMIS‐Depression T scores ( r = 0.43, P = 0.001), as well as Pain interference, Pain behaviors, Fatigue, Sleep disturbance, Sleep impairment, and Social isolation T scores ( r s = 0.38 to −0.51, P s < 0.01). These results demonstrate that more severe PTSD was associated with greater pain, severe depressive symptoms, worse physical health status, and greater pain‐related interference, as expected from other study findings …”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…Additionally, theta scores were positively associated with PROMIS‐Depression T scores ( r = 0.43, P = 0.001), as well as Pain interference, Pain behaviors, Fatigue, Sleep disturbance, Sleep impairment, and Social isolation T scores ( r s = 0.38 to −0.51, P s < 0.01). These results demonstrate that more severe PTSD was associated with greater pain, severe depressive symptoms, worse physical health status, and greater pain‐related interference, as expected from other study findings …”
Section: Resultssupporting
confidence: 88%
“…The current study found that higher PTSD symptom severity (theta) was associated with poorer health status across multiple domains, specifically in sleep ( r s = 0.38 and 0.51), social ( r s = −0.45, −0.44, and 0.51), depression ( r = 0.43), and fatigue or other health issues ( r s = 0.33 to −0.41), which are consistent with previous findings . Additionally, theta scores were positively associated with ratings for worst pain.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations